Feasibility Study JRH Supergrip Battery Cable Clamp - Ramos, Jun D.C.; Clemente, Daniel F.; Gaffud, Ryan M. (Diliman, Quezon City College of Engineering, 1997)
The group performed a market feasibility study on the JRH-Supergrip. This product is a battery clamp intended to ensure electrical conductivity throughout the car. While ensuring swift electrical connection and disconnection, it also acts as an anti-theft device. The group focused its study to the Philippine setting and gathered data on the determinants for the demand. The main determinant was of course the number of car registry renewals per year. It was found that the car registry renewal was highly linear with a coefficient of correlation of 0.9908. The group hence used a simple linear regression to determine the renewals for the next five years. Along with renewals, other determinants were economic and industry information. With the use of the transport and supply data from DTI and other government institutions, the group forecasted supply and demand and found out that the gap for the next five years would average about 10%. Unsatisfied with the supply demand gap share, the group interviewed car owners to see if they would be willing to buy the product. 90% of the interviewees indicated that they would be willing to buy it at an average price of P75. The marketing strategy recommends an extremely aggressive promotional strategy backed by true quality and coupled with medium price. A large promotional budget was recommended as the main problem now was not the potential demand but was the awareness of the product. The group found that the product contained the following successful venture criteria: it had a present market, it had a growth potential and it had a very low risk. In the technical study, the group evaluated forging and casting alternatives for production. The group chose the forged product in which the main part is to be subcontracted from Cebu due t the perceived quality and functionability of the process output. The group determined the new machine requirements and found out that there was no need to buy new machines for the 2nd to the 5th year of operation. Land requirements were found to be about 200 meters and the total investment cost was at P3.6 million. The designed plant layout was suggested to remain in the original operating site situated at 81 Gerry Angeles, Valenzuela. The group recommended a new organizational structure for the chosen technological alternative. In the financial study, the group calculated the project cost and determined a sum amounting over P20 million. Since this was a very large sum and that the proprietor does not have enough properties to back his loan, an amount which is sufficient to cover three months of operating expenses such as direct material and labor plus the necessary capital investments totaling P 8.7 million was suggested as the amount to be loaned. The repayment period is scheduled monthly for 12 months at an annual interest rate of 27%. Positive cash flow for each year is assured with this setting. Using the projected cash flow as an input data, an Internal Rate of Return of 46% was calculated which is greater than the management?s minimum attractive rate of return of only 20%, thus verifying it profitability. The Payback period for the project is 2 years and two and a half months which is less than the five year project period. Critical financial statements such as Absorption Income Statement and Balance Sheet for the next five years were projected. Net Income for the first year is over P4.8 million which continuously increases to P5.8 million on the last year. Projected balance sheets also were favorable in the sense that total assets were consistently increasing having most of its bulk tied up in cash. This ensured protection against the business? liabilities. The legal structure of the business is a sole proprietorship which is consistent with the plans of the product inventor. The recommended organizational structure had a horizontal structure. Here, each section is encouraged to take initiative and not depend so much on the president. All in all, the business will employ 15 direct labors, 2 office assistants, 4 supervisors, and 3 vice presidents. Finally, the group evaluated the project to be socially profitable with several sectors benefiting such as the suppliers, distributors, the public, government, the transport industry and most importantly, the laborers, hence contributing significantly to the nation?s need for more jobs.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Battery industry; Automobiles--Electric equipment; Participatory monitoring and evaluation (Project management)